Chatbots and the Pursuit of Artificial General Intelligence. - KASSAN, PETER (Skeptic, 2024)
The article focuses on critiquing the perception that large language models (LLMs) like ChatGPT represent significant progress towards achieving artificial general intelligence (AGI). It argues that despite their impressive ability to generate human-like text, chatbots lack genuine understanding and intelligence. It also emphasizes the statistical nature of chatbots responses.